2002
DOI: 10.1046/j.1523-1755.2002.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cyclosporine-induced tubulointerstitial lesions in children with minimal change nephrotic syndrome

Abstract: Duration of the CsA treatment and the duration of heavy proteinuria during CsA treatment were independent significant risk factors for the development of CsA-induced tubulointerstitial lesions in children with MCNS who had been treated with long-term moderate-dose CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
4
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 14 publications
0
97
4
2
Order By: Relevance
“…Tubular atrophy associated with striped interstitial fibrosis, a typical feature CsA nephrotoxicity (Inoue et al 1999;Iijima et al 2002;Nakahata et al 2005), was not found in any of the study subjects, except one patient with SRNS. The patient with FSGS (Patient 8) showed interstitial lesions, however, there were mild and graded as group II, and the overall picture suggested a tendency towards improvement as compared to the pretreatment renal biopsy findings (Table 2).…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Tubular atrophy associated with striped interstitial fibrosis, a typical feature CsA nephrotoxicity (Inoue et al 1999;Iijima et al 2002;Nakahata et al 2005), was not found in any of the study subjects, except one patient with SRNS. The patient with FSGS (Patient 8) showed interstitial lesions, however, there were mild and graded as group II, and the overall picture suggested a tendency towards improvement as compared to the pretreatment renal biopsy findings (Table 2).…”
Section: Resultsmentioning
confidence: 77%
“…However, CsA nephrotoxicity remains a major problem (Habib and Niaudet 1994;Inoue et al 1999;Iijima et al 2002). In this conventional CsA treatment protocol for NS, Inoue et al (1999) reported that a young age at the start of CsA treatment and a higher frequency of relapses during CsA treatment might be risk factors for the development of chronic CsA nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations